Cystitis infection by E.coli - adel, Lina (faculty of Basic Medical Science - Libyan International Medical University, 2020)
A urinary tract infection (UTIs) are one of the most common pathological conditions in both community and hospital settings. Among the common uropathogens cause that associated to UTIs, UroPathogenic Escherichia coli (UPEC) is the primary cause it is one of the most common bacterial infections, UPEC strains possess large number of both structural (as fimbriae, pili , curli, flagella) and secreted (toxins, iron-acquisition systems) virulence factors that contribute to their capacity to cause disease, although the ability to adhere to the host epithelial cells in the urinary tract represents the most important determinant of pathogenicity. On the opposite side, the bladder epithelium shows a multifaceted array of host defenses including the urine flow and the secretion of antimicrobial substances, which represent useful tools to counteract bacterial infections. A vast amount of literature regarding the mechanism through which E.coli induces cystitis accounts for 95% of visits to physicians for symptoms of urinary tract infection. is defined as significant bacteriuria in the setting of symptoms of cystitis or pyelonephritis, It is pathogenic inflammation of the upper or lower urinary tract. Women are more commonly afflicted with UTIs and caused by common pathogens such as Escherichia coli (86%).
The urinary system is the body's drainage system for removing wastes and extra water. It includes two kidneys, two ureters, a bladder, and a urethra. Urinary tract infections (UTIs) are the second most common type of infection in the body (1). (UTIs) are considered to be the most frequent bacterial infections and they are common in females because women have shorter urethras proximately 90% of first urinary tract infections in young women and In women the lower third of the urethra is continually contaminated with pathogens from the vagina and the rectum, and it can become a serious health problem if the infection spreads to your kidneys.